AN OVERVIEW OF THE TOTAL NUMBER OF SALIVARY BACTERIA BASED ON THE NUTRITIONAL STATUS OF CHILDREN - Algamar, Danty; Anggarani, Welly; Rohmah, Yayun Siti; Amalina, Rizki (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: A person's nutritional status can affect oral health where socio-economic status had a close relationship with the nutritional fulfillment. About 34% of the population of Bandarharjo North Semarang Village is unemployed, which requires monitoring the nutritional status of children in the area. Nutritional status can affect the risk of caries in children, where the lower a person's nutritional status, the higher the risk of caries. This study aimed to determine the total number of salivary bacteria based on the nutritional status of children aged 5-12 years at SDN Bandarharjo 02.Method: This study used descriptive observations, by taking 2-5 ml of unstimulated saliva in 100 children aged 5-12 years who had been measured nutritional status based on BMI/A. The saliva samples obtained were then counted for total bacteria with a colony counter. Data was analyzed using univariate analysis.Result: The results showed that from 100 children aged 5-12 years, the average total number of bacteria was 43.76 ± 43.22 CFU/ml. The total number of bacteria in 22 children with overweight status was 45.95 ± 18.78 CFU/ml, 62 children with normal status 37.51 ± 42.47 CFU/ml, 16 children with thinnes status 64.93 ± 62.04 CFU/ml.Conclusion: Based on the results of the study, he highest total number of bacteria was found in the group of children with thinnes status